RNA Sequencing Reveals Xyr1 as a Transcription Factor Regulating Gene Expression beyond Carbohydrate Metabolism. (27th December 2016) - Ma, Liang; Chen, Ling; Zhang, Lei; Zou, Gen; Liu, Rui; Jiang, Yanping; Zhou, Zhihua
Abstract : Xyr1 has been demonstrated to be the main transcription activator of (hemi)cellulases in the well-known cellulase producer Trichoderma reesei . This study comprehensively investigates the genes regulated by Xyr1 through RNA sequencing to produce the transcription profiles of T. reesei Rut-C30 and its xyr1 deletion mutant (Δ xyr1 ), cultured on lignocellulose or glucose. xyr1 deletion resulted in 467 differentially expressed genes on inducing medium. Almost all functional genes involved in (hemi)cellulose degradation and many transporters belonging to the sugar porter family in the major facilitator superfamily (MFS) were downregulated in Δ xyr1 . By contrast, all differentially expressed protease, lipase, chitinase, some ATP-binding cassette transporters, and heat shock protein-encoding genes were upregulated in Δ xyr1 . When cultured on glucose, a total of 281 genes were expressed differentially in Δ xyr1, most of which were involved in energy, solute transport, lipid, amino acid, and monosaccharide as well as secondary metabolism. Electrophoretic mobility shift assays confirmed that the intracellular β -glucosidase bgl2, the putative nonenzymatic cellulose-attacking gene cip1, the MFS lactose transporter lp, the nmrA-like gene, endo T, the acid protease pepA, and the small heat shock protein hsp23 were probable Xyr1-targets. These results might help elucidate the regulation system for synthesis and secretion of (hemi)cellulases in T. reesei Rut-C30.